Chronic pain conditions and use of analgesics among nursing home patients with dementia. Issue 5 (21st May 2023) - Myrenget, Martin Elstad; Borchgrevink, Petter C.; Rustøen, Tone; Butler, Stephen; Thorsvik, Dagfinn; Småstuen, Milada C.; Sandvik, Reidun
Abstract : Supplemental Digital Content is Available in the Text. Two-thirds of patients with dementia in nursing homes had chronic pain, and by thorough clinical examination, half of these had pain without known cause. Abstract: Pain management for patients with dementia is challenging because many experience pain while being unable to communicate their pain. The aim of this study was to describe pain, pain management, and to perform a thorough clinical examination of chronic pain conditions among patients with dementia. Residents (n = 498) from 12 nursing homes were assessed for dementia (Clinical Dementia Rating scale [CDR]) and for pain with the Mobilization-Observation-Behavior-Intensity-Dementia-2 (MOBID-2) assessment form. Of all examined nursing home patients with dementia, 68% had moderate or severe chronic pain. The final study population (n = 262) with a CDR score of ≥1 and a MOBID-2 score of ≥3 were examined by pain expert physicians for chronic pain and categorized according to the International Classification of Disease (ICD-10/-11) classification systems. More than half (54.6%) had chronic pain conditions without underlying disease classified as chronic primary pain by ICD-11. Chronic widespread pain was the most prevalent (14.5%) followed by nonspecific pain from the back (13.4%), whereas the most prevalent chronic secondary pain conditions were chronic pain caused by osteoarthritis (15.4%) and stroke (8.0%). One-fourth received opioids, which was significantly associated with severe pain ( P < 0.001) compared with moderate pain, although no significant association was found between opioid use and the type of pain condition. Although knowledge of the severity and specific types of pain conditions is recommended to direct the choice of treatment, these areas are not sufficiently explored in the nursing home populations with dementia and may hinder a better treatment of pain in this population.